1998
DOI: 10.1017/s0890037x00043980
|View full text |Cite
|
Sign up to set email alerts
|

Control of Downy Brome (Bromus tectorum) with Herbicides and Perennial Grass Competition

Abstract: Long-term control of downy brome with an integrated approach is needed in order to sustain range productivity. Studies were conducted to study the effectiveness of a combination of downy brome control practices. In two studies, glyphosate and paraquat were evaluated at various rates for up to three successive years for control of downy brome in rangeland. A third study evaluated the competitiveness of perennial cool-season grasses against downy brome in the absence of herbicides. Glyphosate, at 0.55 kg/ha, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
48
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(49 citation statements)
references
References 12 publications
1
48
0
Order By: Relevance
“…Where cheatgrass is already abundant, it could possibly be directly controlled, but also precluded from further expansion by landscaping areas of untended vegetation, planting invasion-resistant native vegetation, or avoiding burning where cheatgrass is present or could disperse. Some studies have shown that planting of certain perennials may help to prevent further establishment and invasion of cheatgrass (Whitson and Koch 1998;Monaco et. al.…”
Section: Discussionmentioning
confidence: 99%
“…Where cheatgrass is already abundant, it could possibly be directly controlled, but also precluded from further expansion by landscaping areas of untended vegetation, planting invasion-resistant native vegetation, or avoiding burning where cheatgrass is present or could disperse. Some studies have shown that planting of certain perennials may help to prevent further establishment and invasion of cheatgrass (Whitson and Koch 1998;Monaco et. al.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore methods to reduce cheatgrass densities are necessary. Proposed techniques include herbicides imazapic (Plateau) (Shinn and Thill 2002) and glyphosate (Whitson and Koch 1998), defoliation via livestock grazing (Hulbert 1955, Finnerty and Klingman 1961, Mosley 1996, pathogenic bacteria (Kennedy et al 1991) and fungi (Meyer et al 2001). Although prescribed fire alone is not recommended (Mosley et al 1999), it may be an effective technique worth investigation if applied in combination with a spring glyphosate treatment and conducted either in late spring or autumn.…”
Section: Status and Trends Of Sagebrush Ecosystems 7 -49mentioning
confidence: 99%
“…One technique that has proven effective for brome control is planting highly competitive, non-native perennial grasses, such as pubescent wheatgrass (Thinopyrum intermedium Host. Barkworth & Dewey) or crested wheatgrass (Agropyron desertorum L.) Whitson and Koch 1998). However, grass competition, particularly from competitive non-natives, hinders the establishment of other plant functional groups, such as forbs and shrubs (Hild et al 2006;Redente et al 1984).…”
mentioning
confidence: 99%